Cardiovascular diseases in patients with psoriasis in clinical practice: case report. Eurasian heart journal - O. A. Kuzmina; O. Iu. Mironova; V. V. Fomin (Евразийский Кардиологический Журнал, 2022)
Psoriasis is a genetically determined multifactorial disease that affects about 2% of the population. According to modern concepts of this disease, the level of comorbid diseases, especially those associated with damage to the cardiovascular system, is high. This article presents a clinical case of severe disseminated psoriasis vulgaris, progressive stage, mixed form in a patient with a very high cardiovascular risk. The uniqueness of this clinical case lies in the combined course of psoriasis and such comorbid diseases as: severe hypertension, obesity, dyslipidemia, type 2 diabetes mellitus (DM), hyperuricemia. The main clinical manifestations were the presence of widespread lesions on the patient’s skin, episodes of discomfort behind the sternum during physical activity, as well as destabilization of blood pressure numbers (maximum rise to 180/100 mm Hg). As part of the hospitalization in the skin clinic, the patient underwent topical ointment therapy with the use of glucocorticoid ointments, ointments containing salicylic acid, PUVA therapy, as a result of which the skin process showed positive dynamics with regression of lesions by 90-100% with an outcome in residual hyperpigmentation, no new lesions were noted. During hospitalization to a therapy department, the optimal antihypertensive, lipid-lowering, uricosuric, hypoglycemic therapy was selected, as a result of which it was possible to achieve an improvement in the patient’s condition, stabilization of blood pressure at the level of 130-140/70 mm Hg. So patients with psoriasis require careful assessment of cardiovascular risk in clinical practice. A multidisciplinary approach will not only improve the quality of life of patients, reduce the likelihood of major cardiovascular events, but also increase life expectancy and reduce mortality.